An Update on Medical Management of Thyroid Eye Disease with Insights on Teprotumumab - Smriti Dabas; Nishi Meghna Satish; Sangeeta Abrol (Delhi Journal of Ophthalmology)
Thyroid eye disease (TED) is a debilitating autoimmune condition. It occurs most commonly with the hyperthyroid state but can also be seen in euthyroid and hypothyroid states. Corticosteroids, steroid-sparing agents, and biologicals have been used, although none of them were Food and Drug Administration (FDA) approved, with the recent exception of teprotumumab. Teprotumumab was FDA approved for the treatment of TED in January 2020. It has been shown to be effective in reducing proptosis, which was not possible with the other medications available. A detailed review of the literature regarding the medical treatment of TED was done. A comprehensive update on the management options was compiled, with particular emphasis on teprotumumab. Treatment of TED remains a challenge as there is no standard protocol for the same. This article aimed to review the medical management of TED, with an emphasis on teprotumumab.